A wear-resistant high-strength polyoxymethylene sheet and preparation method thereof

By introducing Si-H bonds and oxetane structures into polyformaldehyde plates, a cross-linking network and self-healing mechanism is formed, the problems of flammability and wear resistance of polyformaldehyde plates are solved, and their flame retardant properties and wear resistance are significantly improved, and their self-healing functions are provided.

CN119432000BActive Publication Date: 2025-04-04GUANGDONG MENGXIN PLASTIC IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510024710.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-04
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

Existing polyformaldehyde plates are extremely combustible when used as building materials, and their wear resistance is not sufficient to adapt to complex and harsh use environments.

Method used

Wear-resistant high-strength polyformaldehyde sheets are obtained by melting and mixing materials such as copolyformaldehyde, 3-chloromethyl-3-methyloxetane and modified cubic boron nitride. The plate introduces Si-H bonds and oxetane structures at the molecular level to form a cross-linking network and a self-healing mechanism to improve its flame retardant performance and wear resistance.

Benefits of technology

It significantly improves the flame retardant performance and wear resistance of polyformaldehyde sheets, enhances its service life and safety in complex environments, and also has self-healing functions, further improving the performance of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a wear-resistant high-strength polyoxymethylene sheet and a preparation method thereof, and relates to the technical field of polymer materials. When preparing the wear-resistant high-strength polyoxymethylene sheet, the present invention reacts copolymerized polyoxymethylene and 3-chloromethyl-3-methyloxetane to obtain modified polyoxymethylene; polymerizes and coats bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione on cubic boron nitride to obtain modified cubic boron nitride; reacts bamboo fiber and allyltriethoxysilane to obtain modified bamboo fiber; melt-mixes the modified polyoxymethylene, modified cubic boron nitride and modified bamboo fiber, and performs injection molding to obtain the wear-resistant high-strength polyoxymethylene sheet. The wear-resistant high-strength polyoxymethylene sheet prepared by the present invention has excellent wear resistance, flame retardancy, antibacterial and self-repairing properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a wear-resistant high-strength polyoxymethylene plate and a preparation method thereof. Background Art

[0002] Polyoxymethylene (POM) is one of the five major engineering plastics with good physical and mechanical properties and processing properties. Its specific strength and specific stiffness are close to those of metals. It is widely used in electronic appliances, machinery manufacturing, automobiles, construction and other industries, replacing traditional metal materials such as steel, iron, copper, and aluminum. Polyoxymethylene sheets are sheets of different shapes and thicknesses obtained by extruding polyoxymethylene plastic particles through an extruder at high temperature, extruding or injection molding through the corresponding die mouth. They can be used as building materials such as doors and windows, floors, and wall panels. They have the advantages of light weight, pollution resistance, and easy cleaning. However, the limiting oxygen index of polyoxymethylene is only 15%, which is extremely flammable and poses a great safety hazard when used as a building material; polyoxymethylene itself has certain self-lubricity and wear resistance, but when used as a building material, especially a floor material, higher requirements are placed on the wear resistance of polyoxymethylene. How to further improve the wear resistance of polyoxymethylene sheets and adapt to more complex and harsh use environments is an urgent problem to be solved. Based on the above problems, it is necessary to invent a high-strength polyoxymethylene sheet with excellent flame retardancy and wear resistance. Summary of the invention

[0003] The object of the present invention is to provide a wear-resistant high-strength polyoxymethylene plate and a preparation method thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a wear-resistant high-strength polyoxymethylene plate, wherein the wear-resistant high-strength polyoxymethylene plate is prepared by reacting copolymerized polyoxymethylene and 3-chloromethyl-3-methyloxetane to obtain modified polyoxymethylene; the modified polyoxymethylene, modified cubic boron nitride and modified bamboo fiber are melt-mixed and injection-molded to obtain the wear-resistant high-strength polyoxymethylene plate; the copolymerized polyoxymethylene is prepared by reacting tripolyoxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, N,N- The modified cubic boron nitride is prepared by ring-opening polymerization of dimethyl-1-(oxiran-2-yl)methylamine; the modified cubic boron nitride is prepared by polymerizing bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione and coating them on cubic boron nitride; the modified bamboo fiber is prepared by reacting bamboo fiber and allyltriethoxysilane; the bamboo fiber is prepared by purifying bamboo powder with an alkali treatment solution.

[0005] A method for preparing a wear-resistant high-strength polyoxymethylene sheet, the method comprising the following preparation steps:

[0006] (1) Add trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(2-oxirane-1-yl)methylamine in a molar ratio of 1:(0.05-0.07):(0.06-0.08) into a reactor, stir at 68-70°C and 100-200 r / min for 30-40 min under nitrogen protection, add initiator at a mass of 0.006-0.008 times the mass of trioxymethylene, continue stirring for 5-6 h, and add 0.01 The reaction was terminated by adding ~0.012 times of triethylamine, cooled to room temperature, washed with anhydrous ethanol and deionized water for 3 to 5 times respectively, and dried at 58 to 62°C for 8 to 10 hours under vacuum conditions to obtain copolymer formaldehyde; copolymer formaldehyde, 3-chloromethyl-3-methyloxetane, and hexafluoroisopropanol were mixed uniformly in a mass ratio of 1: (0.6 to 0.8): (6 to 7), stirred at 55 to 57°C and 60 to 80 r / min for 2 to 3 hours, and dried at 66 to 70°C for 8 to 10 hours under vacuum conditions to obtain modified polyformaldehyde;

[0007] (2) Mix cubic boron nitride, triphenylphosphine and toluene in a mass ratio of 1: (0.05-0.07): (38-40), ultrasonically disperse for 50-60 min, add reaction solution 8-10 times the mass of cubic boron nitride, stir at 98-102°C and 200-300 r / min for 3-4 h, filter, wash with anhydrous ethanol and deionized water for 3-5 times each, and dry at 69-71°C under vacuum conditions for 8-10 h to obtain modified cubic boron nitride;

[0008] (3) Mix bamboo powder and alkali treatment liquid at a mass ratio of 1: (12-14), ultrasonically disperse for 1-1.2 hours, filter, wash with deionized water until the filtrate is neutral, and dry at 66-70°C for 8-10 hours under vacuum conditions to obtain bamboo fiber; mix bamboo fiber and anhydrous ethanol at a mass ratio of 1: (40-50), ultrasonically disperse for 20-30 minutes, add 18-20 times the mass of bamboo fiber allyl silane hydrolyzate, stir at 66-70°C, 200-300 r / min for 4-5 hours, filter, wash with anhydrous ethanol 3-5 times, and dry at 72-74°C for 9-11 hours under vacuum conditions to obtain modified bamboo fiber;

[0009] (4) Weigh 98-102 parts of modified polyoxymethylene, 4-5 parts of modified cubic boron nitride, 6-8 parts of modified bamboo fiber, and 0.6-1 part of chloroplatinic acid by mass; add the modified polyoxymethylene, modified cubic boron nitride, modified bamboo fiber, and chloroplatinic acid into a screw extruder for injection molding. After injection molding, keep the temperature at 78-80°C for 2-3 hours, cool to room temperature, and demold to obtain a wear-resistant and high-strength polyoxymethylene sheet.

[0010] As an optimization, the CAS number of the N,N-dimethyl-1-(2-oxirane-1-yl)methylamine in step (1) is: 13222-40-7; the structural formula is: .

[0011] As an optimization, the initiator in step (1) is one of boron trifluoride ethyl ether complex and boron trifluoride butyl ether complex.

[0012] As an optimization, the particle size of the cubic boron nitride in step (2) is 3000 mesh, and the manufacturer is Nangong Jiuxin New Material Technology Co., Ltd.

[0013] As an optimization, the preparation method of the reaction solution in step (2) is: add bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in a molar ratio of 1:(0.8~0.9) to toluene with a mass 5~6 times that of bis(4-carboxyphenyl)phenylphosphine oxide, and mix them evenly to prepare a reaction solution.

[0014] As an optimization, the particle size of the bamboo powder in step (3) is 1200 mesh, and the manufacturer is Lingshou County Yaoyang Mineral Products Processing Plant.

[0015] As an optimization, the preparation method of the alkaline treatment solution in step (3) is: sodium hydroxide, urea, and deionized water are uniformly mixed in a mass ratio of 1: (1.2~1.3): (9~10) to prepare an alkaline treatment solution.

[0016] As an optimization, the preparation method of the allyl silane hydrolyzate in step (3) is as follows: allyl triethoxy silane and anhydrous ethanol are uniformly mixed in a mass ratio of 1: (40-44), the pH is adjusted to 4.8-5.2 with an aqueous solution of oxalic acid with a molar concentration of 1 mol / L, and the mixture is stirred at 10-30° C. and 200-300 r / min for 20-22 min to prepare the allyl silane hydrolyzate.

[0017] As an optimization, the process parameters of the injection molding in step (4) are as follows: setting the extruder barrel temperature to 170-180°C, the screw speed to 80-100 r / min, the injection temperature to 180-184°C, the injection pressure to 50-60 MPa, the holding time to 14-16 s, and the mold temperature to 78-80°C.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: when preparing the wear-resistant high-strength polyoxymethylene sheet, the present invention performs ring-opening polymerization of trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane and N,N-dimethyl-1-(oxirane-2-yl)methylamine to obtain copolymerized polyoxymethylene; the copolymerized polyoxymethylene and 3-chloromethyl-3-methyloxetane are reacted to obtain modified polyoxymethylene; bis(4-carboxyphenyl)phenylphosphine oxide, 1,3 -Bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione is polymerized and coated on cubic boron nitride to obtain modified cubic boron nitride; bamboo powder is purified by alkali treatment liquid to obtain bamboo fiber; bamboo fiber and allyltriethoxysilane are reacted to obtain modified bamboo fiber; modified polyoxymethylene, modified cubic boron nitride and modified bamboo fiber are melt-mixed and injection-molded to obtain wear-resistant and high-strength polyoxymethylene sheet.

[0019] First, tripolyformaldehyde, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(2-oxirane-1)methylamine are ring-opening polymerized to prepare copolymerized tripolyformaldehyde; siloxane, Si-H bond, and tertiary amine structure are introduced into the side chain of copolymerized tripolyformaldehyde molecule; the bond energy of Si-O bond is greater than that of CO bond and CC bond, and siloxane will undergo thermal decomposition reaction at high temperature, absorbing a large amount of heat, and will also promote the carbonization of polymer materials to form a dense carbon layer, preventing further combustion of the material, and improving the flame retardant properties of wear-resistant and high-strength tripolyformaldehyde sheet; Si-H bond can undergo silanization-hydrogenation reaction with carbon-carbon double bonds on modified cellulose and modified cubic boron nitride to form a cross-linked network, inhibiting the carbonization between tripolyformaldehyde molecular chains. Relative slip makes it not easily torn by external shear force, thus improving the wear resistance of the wear-resistant and high-strength polyformaldehyde sheet; the tertiary amine structure introduced on the side chain of the copolymer formaldehyde molecule reacts with the chlorine atom on 3-chloromethyl-3-methyloxetane to obtain modified polyformaldehyde, a quaternary ammonium salt structure is generated on the side chain of the modified polyformaldehyde molecule, and an oxetane structure is introduced; when cracks and scratches appear on the wear-resistant and high-strength polyformaldehyde sheet, under the action of ultraviolet light, the oxetane structure will undergo a ring-opening reaction and combine with the polyformaldehyde molecular chain and the free -CO· free radicals and -C· free radicals on the cellulose to form new chemical bonds, thereby achieving a self-repairing effect; the introduction of the quaternary ammonium salt structure can improve the mildew and antibacterial properties of the wear-resistant and high-strength polyformaldehyde sheet.

[0020] Secondly, the carboxyl group on bis(4-carboxyphenyl)phenylphosphine oxide reacts with the epoxy group on 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, polymerizes and coats on cubic boron nitride to obtain modified cubic boron nitride, and phosphorus element, cyanuric acid structure and carbon-carbon double bond are introduced on the surface of modified cubic boron nitride; the cyanuric acid structure will decompose when heated to produce non-flammable gas (nitrogen, carbon dioxide, water vapor), dilute the oxygen concentration, and improve the flame retardant properties of wear-resistant and high-strength polyoxymethylene sheet; phosphorus element can capture free radicals to form The protective layer can be formed to further improve the flame retardant properties of the wear-resistant high-strength polyformaldehyde sheet; the carbon-carbon double bond introduced on the modified cubic boron nitride can undergo a silyl hydrogen addition reaction with the Si-H bond introduced on the side chain of the modified polyformaldehyde molecule to increase the cross-linking site and improve the wear resistance of the wear-resistant high-strength polyformaldehyde sheet; cubic boron nitride is an inorganic non-metallic material with a hardness second only to diamond and has excellent flame retardancy. The cubic boron nitride is modified to improve the compatibility of cubic boron nitride with resin, reduce agglomeration, give full play to the excellent performance of cubic boron nitride, and further improve the wear resistance and flame retardancy of the wear-resistant high-strength polyformaldehyde sheet.

[0021] Finally, the bamboo powder is purified with an alkaline treatment liquid to remove impurities such as lignin and hemicellulose to obtain bamboo fiber; the bamboo fiber and allyltriethoxysilane are reacted to obtain modified bamboo fiber, and carbon-carbon double bonds are introduced into the modified bamboo fiber. The carbon-carbon double bonds introduced into the modified bamboo fiber can undergo addition reaction with the Si-H bonds introduced into the side chains of the modified polyformaldehyde molecules to form a cross-linked network, thereby inhibiting the relative slip between the polyformaldehyde molecular chains, making it less likely to be torn by external shear forces, and improving the wear resistance of the wear-resistant and high-strength polyformaldehyde board; bamboo fiber is obtained from naturally grown bamboo and is a natural renewable resource. Using bamboo fiber to replace part of petrochemical raw materials can reduce the use of fossil raw materials, be green and environmentally friendly, and save resources. DETAILED DESCRIPTION

[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] A method for preparing a wear-resistant high-strength polyoxymethylene sheet, the method comprising the following preparation steps:

[0025] (1) Add triformaldehyde, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(2-oxirane-1-yl)methylamine in a molar ratio of 1:0.05:0.06 into a reactor, stir at 68°C and 100 r / min for 40 min under nitrogen protection, add boron trifluoride ether complex (0.006 times the mass of triformaldehyde), continue stirring and react for 6 h, and add triformaldehyde. The reaction was terminated by adding 0.01 times of triethylamine, cooled to room temperature, washed with anhydrous ethanol and deionized water for 3 times, and dried at 58°C for 10 hours under vacuum conditions to obtain copolymer formaldehyde; copolymer formaldehyde, 3-chloromethyl-3-methyloxetane and hexafluoroisopropanol were mixed uniformly in a mass ratio of 1:0.6:6, stirred at 55°C and 60r / min for 3 hours, and dried at 66°C for 10 hours under vacuum conditions to obtain modified polyformaldehyde;

[0026] (2) Add bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in a molar ratio of 1:0.8 to toluene with a mass ratio of 5 times that of bis(4-carboxyphenyl)phenylphosphine oxide, and mix them evenly to prepare a reaction solution; mix cubic boron nitride, triphenylphosphine, and toluene evenly in a mass ratio of 1:0.05:38, ultrasonically disperse for 50 minutes, add the reaction solution with a mass ratio of 8 times that of cubic boron nitride, stir at 98°C and 200 r / min for 4 hours, filter, wash with anhydrous ethanol and deionized water 3 times each, and dry at 69°C under vacuum conditions for 10 hours to obtain modified cubic boron nitride;

[0027] (3) Sodium hydroxide, urea and deionized water were mixed in a mass ratio of 1:1.2:9 to prepare an alkali treatment solution; bamboo powder and alkali treatment solution were mixed in a mass ratio of 1:12, ultrasonically dispersed for 1 hour, filtered, washed with deionized water until the filtrate was neutral, and dried at 66°C for 10 hours under vacuum conditions to obtain bamboo fiber; allyl triethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:40, the pH was adjusted to 4.8 with an oxalic acid aqueous solution with a molar concentration of 1 mol / L, and stirred at 10°C and 200 r / min for 22 minutes to prepare an allyl silane hydrolyzate; bamboo fiber and anhydrous ethanol were mixed in a mass ratio of 1:40, ultrasonically dispersed for 20 minutes, and 18 times the mass of bamboo fiber was added. The allyl silane hydrolyzate was stirred at 66°C and 200 r / min for 5 hours, filtered, washed with anhydrous ethanol for 3 times, and dried at 72°C for 11 hours under vacuum conditions to obtain modified bamboo fiber;

[0028] (4) Weigh 98 parts of modified polyoxymethylene, 4 parts of modified cubic boron nitride, 6 parts of modified bamboo fiber, and 0.6 parts of chloroplatinic acid by mass; add the modified polyoxymethylene, modified cubic boron nitride, modified bamboo fiber, and chloroplatinic acid into a screw extruder for injection molding, and set the extruder barrel temperature to 170°C, the screw speed to 80 r / min, the injection temperature to 180°C, the injection pressure to 50 MPa, the holding time to 16 s, the mold temperature to 78°C, keep the temperature at 78°C for 3 h, cool to room temperature, and demold to obtain a wear-resistant and high-strength polyoxymethylene sheet.

[0029] Example 2

[0030] A method for preparing a wear-resistant high-strength polyoxymethylene sheet, the method comprising the following preparation steps:

[0031] (1) Add triformaldehyde, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(2-oxirane-1-yl)methylamine in a molar ratio of 1:0.06:0.07 into a reactor, stir at 69°C and 150 r / min for 35 min under nitrogen protection, add 0.007 times the mass of triformaldehyde in boron trifluoride ether complex, continue stirring and reacting for 5.5 h, and add triformaldehyde in a molar ratio of 1:0.06:0.07. The reaction was terminated with 0.011 times of triethylamine, cooled to room temperature, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 9 hours under vacuum conditions to obtain copolymer formaldehyde; copolymer formaldehyde, 3-chloromethyl-3-methyloxetane, and hexafluoroisopropanol were mixed evenly in a mass ratio of 1:0.7:6.5, stirred at 56°C and 70r / min for 2.5 hours, and dried at 68°C for 9 hours under vacuum conditions to obtain modified polyformaldehyde;

[0032] (2) Add bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in a molar ratio of 1:0.85 to toluene (5.5 times the mass of bis(4-carboxyphenyl)phenylphosphine oxide), and mix them evenly to prepare a reaction solution; mix cubic boron nitride, triphenylphosphine, and toluene in a mass ratio of 1:0.06:39, ultrasonically disperse for 55 minutes, add the reaction solution (9 times the mass of cubic boron nitride), stir and react at 100°C and 250 r / min for 3.5 hours, filter, wash with anhydrous ethanol and deionized water 4 times each, and dry at 70°C under vacuum conditions for 9 hours to obtain modified cubic boron nitride;

[0033] (3) Sodium hydroxide, urea and deionized water were mixed in a mass ratio of 1:1.25:9.5 to prepare an alkali treatment solution; bamboo powder and alkali treatment solution were mixed in a mass ratio of 1:13, ultrasonically dispersed for 1.1 hours, filtered, washed with deionized water until the filtrate was neutral, and dried at 68°C under vacuum for 9 hours to obtain bamboo fiber; allyl triethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:42, and dried with a molar concentration of 1 mol / L grass The acid aqueous solution was adjusted to pH 4.9, stirred at 20°C and 250 r / min for 21 min to prepare an allyl silane hydrolyzate; the bamboo fiber and anhydrous ethanol were mixed at a mass ratio of 1:45, ultrasonically dispersed for 25 min, and allyl silane hydrolyzate 19 times the mass of the bamboo fiber was added, stirred at 68°C and 250 r / min for 4.5 h, filtered, washed with anhydrous ethanol 4 times, and dried at 73°C under vacuum conditions for 10 h to obtain modified bamboo fiber;

[0034] (4) Weigh 100 parts of modified polyoxymethylene, 4.5 parts of modified cubic boron nitride, 7 parts of modified bamboo fiber, and 0.8 parts of chloroplatinic acid by mass; add the modified polyoxymethylene, modified cubic boron nitride, modified bamboo fiber, and chloroplatinic acid into a screw extruder for injection molding, and set the extruder barrel temperature to 175°C, the screw speed to 90 r / min, the injection temperature to 182°C, the injection pressure to 55 MPa, the holding time to 15 s, the mold temperature to 79°C, keep the temperature at 79°C for 2.5 h, cool to room temperature, and demold to obtain a wear-resistant and high-strength polyoxymethylene sheet.

[0035] Example 3

[0036] A method for preparing a wear-resistant high-strength polyoxymethylene sheet, the method comprising the following preparation steps:

[0037] (1) Add triformaldehyde, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(2-oxirane-1-yl)methylamine in a molar ratio of 1:0.07:0.08 into a reactor, stir at 70°C and 200 r / min for 30 min under nitrogen protection, add boron trifluoride ether complex (0.008 times the mass of triformaldehyde), continue stirring and reacting for 5 h, and add triformaldehyde. The reaction was terminated by adding 0.012 times of triethylamine, cooled to room temperature, washed with anhydrous ethanol and deionized water for 5 times, dried at 62°C for 8 hours under vacuum conditions to obtain copolymer formaldehyde; copolymer formaldehyde, 3-chloromethyl-3-methyloxetane and hexafluoroisopropanol were mixed uniformly in a mass ratio of 1:0.8:7, stirred at 57°C and 80r / min for 2 hours, and dried at 70°C for 10 hours under vacuum conditions to obtain modified polyformaldehyde;

[0038] (2) Add bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in a molar ratio of 1:0.9 to toluene (6 times the mass of bis(4-carboxyphenyl)phenylphosphine oxide), and mix them evenly to prepare a reaction solution; mix cubic boron nitride, triphenylphosphine, and toluene in a mass ratio of 1:0.07:40, ultrasonically disperse for 60 minutes, add the reaction solution (10 times the mass of cubic boron nitride), stir and react at 102°C and 300 r / min for 3 hours, filter, wash with anhydrous ethanol and deionized water 5 times each, and dry at 71°C under vacuum for 8 hours to obtain modified cubic boron nitride;

[0039] (3) Sodium hydroxide, urea and deionized water were mixed in a mass ratio of 1:1.3:10 to prepare an alkali treatment solution; bamboo powder and alkali treatment solution were mixed in a mass ratio of 1:14 to prepare an alkali treatment solution; bamboo powder and alkali treatment solution were mixed in a mass ratio of 1:14 to prepare an alkali treatment solution; the mixture was ultrasonically dispersed for 1.2 hours, filtered, washed with deionized water until the filtrate was neutral, and dried at 70°C for 10 hours under vacuum conditions to prepare bamboo fiber; allyl triethoxysilane and anhydrous ethanol were mixed in a mass ratio of 1:44 to prepare an alkali treatment solution; the mixture was stirred at 30°C and 300 r / min for 20 minutes to prepare an allyl silane hydrolyzate; bamboo fiber and anhydrous ethanol were mixed in a mass ratio of 1:50 to prepare an alkali treatment solution; the mixture was ultrasonically dispersed for 30 minutes; 20 times the mass of the bamboo fiber was added with an allyl silane hydrolyzate; the mixture was stirred at 70°C and 300 r / min for 4 hours, filtered, washed with anhydrous ethanol for 5 times, and dried at 74°C for 9 hours under vacuum conditions to prepare modified bamboo fiber;

[0040] (4) Weigh 102 parts of modified polyoxymethylene, 5 parts of modified cubic boron nitride, 8 parts of modified bamboo fiber, and 1 part of chloroplatinic acid by mass; add the modified polyoxymethylene, modified cubic boron nitride, modified bamboo fiber, and chloroplatinic acid into a screw extruder for injection molding, and set the extruder barrel temperature to 180°C, the screw speed to 100 r / min, the injection temperature to 184°C, the injection pressure to 60 MPa, the holding time to 14 s, the mold temperature to 80°C, keep warm at 80°C for 2 h, cool to room temperature, and demold to obtain a wear-resistant and high-strength polyoxymethylene sheet.

[0041] Comparative Example 1:

[0042] The difference between the preparation method of the wear-resistant high-strength polyoxymethylene plate of Comparative Example 1 and Example 2 lies in the difference in step (1). Step (1) is modified as follows: trioxymethylene and N,N-dimethyl-1-(2-oxirane-1-yl)methylamine are added to a reaction kettle at a molar ratio of 1:0.07, stirred at 69°C and 150 r / min for 35 min under nitrogen protection, and a boron trifluoride ether complex of 0.007 times the mass of trioxymethylene is added, and the reaction is continued with stirring for 5.5 h. , add triethylamine in an amount of 0.011 times the mass of trioxymethylene to terminate the reaction, cool to room temperature, wash with anhydrous ethanol and deionized water 4 times each, dry at 60°C for 9 hours under vacuum conditions to obtain copolymerized polyoxymethylene; mix copolymerized polyoxymethylene, 3-chloromethyl-3-methyloxetane, and hexafluoroisopropanol in a mass ratio of 1:0.7:6.5, stir at 56°C, 70r / min for 2.5 hours, and dry at 68°C for 9 hours under vacuum conditions to obtain modified polyoxymethylene. The remaining steps are the same as those in Example 2.

[0043] Comparative Example 2:

[0044] The preparation method of the wear-resistant high-strength polyoxymethylene sheet of Comparative Example 2 is different from that of Example 2 in step (1). Step (1) is modified as follows: trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane and N,N-dimethyl-1-(2-oxirane-1)methylamine are added to a reaction kettle in a molar ratio of 1:0.06:0.07, stirred at 69°C and 150 r / min for 35 min under nitrogen protection, added with 0.007 times the mass of trioxymethylene boron trifluoride ether complex, continued to stir for 5.5 h, added with 0.011 times the mass of trioxymethylene triethylamine to terminate the reaction, cooled to room temperature, washed with anhydrous ethanol and deionized water 4 times each, and dried at 60°C for 9 h under vacuum conditions to obtain modified polyoxymethylene. The remaining steps are the same as those of Example 2.

[0045] Comparative Example 3:

[0046] The preparation method of the wear-resistant high-strength polyoxymethylene sheet of Comparative Example 3 is different from that of Example 2 in that step (2) is not performed, and step (4) is modified as follows: 100 parts of modified polyoxymethylene, 4.5 parts of cubic boron nitride, 7 parts of modified bamboo fiber, and 0.8 parts of chloroplatinic acid are weighed by mass; the modified polyoxymethylene, cubic boron nitride, modified bamboo fiber, and chloroplatinic acid are added to a screw extruder for injection molding, and the extruder barrel temperature is set to 175° C., the screw speed is set to 90 r / min, the injection temperature is set to 182° C., the injection pressure is set to 55 MPa, the holding time is set to 15 s, the mold temperature is set to 79° C., the temperature is kept at 79° C. for 2.5 h, cooled to room temperature, and demolded to obtain a wear-resistant high-strength polyoxymethylene sheet. The remaining steps are the same as those of Example 2.

[0047] Comparative Example 4:

[0048] The preparation method of the wear-resistant high-strength polyoxymethylene sheet of Comparative Example 4 is different from that of Example 2 in step (3), and step (3) is modified as follows: sodium hydroxide, urea, and deionized water are mixed evenly at a mass ratio of 1:1.25:9.5 to prepare an alkali treatment solution; bamboo powder and the alkali treatment solution are mixed evenly at a mass ratio of 1:13, ultrasonically dispersed for 1.1 hours, filtered, washed with deionized water until the filtrate is neutral, and dried at 68°C for 9 hours under vacuum conditions to obtain modified bamboo fiber. The remaining steps are the same as those of Example 2.

[0049] Test Example 1

[0050] Wear resistance test

[0051] Test method: The wear resistance of the embodiment and the comparative example was measured on an M-200 friction and wear tester according to GB / T3960-2016. The material of the grinding ring in the test was 45# steel, with a radius of 40mm; the size of the sample was 30mm×7mm×6mm; the speed of the lower shaft in the test was 200r / min, the load was 20kg, the grinding was carried out for 2h, and the wear rate was calculated. The results are shown in Table 1.

[0052]

[0053] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 1, it can be found that the wear-resistant high-strength polyoxymethylene sheet prepared by the present invention has good wear resistance.

[0054] By comparison, the wear rates of Examples 1 to 3 are lower than that of Comparative Example 1, indicating that the copolymerized polyformaldehyde is prepared by ring-opening polymerization of trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane and N,N-dimethyl-1-(oxirane-2-yl)methylamine; Si-H bonds are introduced into the side chains of the copolymerized polyformaldehyde molecules; the Si-H bonds can react with the carbon-carbon double bonds on the modified cellulose and the modified cubic boron nitride to form a cross-linked network, thereby inhibiting the relative slip between the polyformaldehyde molecular chains, making it not easily torn by external shear forces, and improving the wear resistance of the wear-resistant and high-strength polyformaldehyde sheet.

[0055] By comparison, the wear rates of Examples 1 to 3 are lower than that of Comparative Example 3, indicating that the carboxyl group on bis(4-carboxyphenyl)phenylphosphine oxide reacts with the epoxy group on 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, polymerizes and coats the reactants on cubic boron nitride to obtain modified cubic boron nitride, and carbon-carbon double bonds are introduced on the surface of the modified cubic boron nitride; the carbon-carbon double bonds introduced on the modified cubic boron nitride can undergo a silylation reaction with the Si-H bonds introduced on the side chains of the modified polyformaldehyde molecules, thereby increasing the cross-linking sites and improving the wear resistance of the wear-resistant and high-strength polyformaldehyde sheet.

[0056] By comparison, the wear rates of Examples 1 to 3 are lower than that of Comparative Example 4, indicating that bamboo powder is purified by an alkali treatment solution to remove impurities such as lignin and hemicellulose to obtain bamboo fiber; bamboo fiber and allyltriethoxysilane are reacted to obtain modified bamboo fiber, and carbon-carbon double bonds are introduced into the modified bamboo fiber. The carbon-carbon double bonds introduced into the modified bamboo fiber can react with the Si-H bonds introduced into the side chains of the modified polyoxymethylene molecules to form a cross-linked network, thereby inhibiting the relative slip between polyoxymethylene molecular chains, making it not easily torn by external shear forces, and improving the wear resistance of the wear-resistant and high-strength polyoxymethylene sheet.

[0057] Test Example 2

[0058] Flame retardant performance test

[0059] Test method: The examples and comparative examples were prepared into standard specimens according to GB / T2406, and the limiting oxygen index of the standard specimens was tested. The results are shown in Table 2.

[0060]

[0061] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 2, it can be found that the wear-resistant and high-strength polyoxymethylene sheet prepared by the present invention has good flame retardant properties.

[0062] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 1, indicating that the copolymerization of trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane and N,N-dimethyl-1-(2-oxirane-1)methylamine is prepared by ring-opening polymerization; siloxane is introduced into the side chain of the copolymerization of trioxymethylene molecules; the bond energy of the Si-O bond is greater than that of the CO bond and the CC bond, and the siloxane will undergo a thermal decomposition reaction at high temperature, absorbing a large amount of heat, and will also promote the carbonization of the polymer material to form a dense carbon layer, thereby preventing further combustion of the material and improving the flame retardant properties of the wear-resistant and high-strength polyoxymethylene sheet.

[0063] By comparison, the limiting oxygen index of Examples 1 to 3 is greater than that of Comparative Example 3, indicating that the carboxyl group on bis(4-carboxyphenyl)phenylphosphine oxide reacts with the epoxy group on 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, polymerizes and coats the reactants on cubic boron nitride to obtain modified cubic boron nitride, and phosphorus element and cyanuric acid structure are introduced on the surface of the modified cubic boron nitride; the cyanuric acid structure decomposes when heated to produce non-flammable gases (nitrogen, carbon dioxide, water vapor), dilutes the oxygen concentration, and improves the flame retardant properties of the wear-resistant and high-strength polyoxymethylene sheet; the phosphorus element can further improve the flame retardant properties of the wear-resistant and high-strength polyoxymethylene sheet by capturing free radicals to form a protective layer.

[0064] Test Example 3

[0065] Antibacterial performance test

[0066] Test method: Cut the examples and comparative examples into 1 cm × 1 cm × 0.4 cm samples, wash them with ethanol and set aside; activate the E. coli strain and prepare it to a concentration of 2x10 4 cfu / ml bacterial suspension, then put the cut sample into the bacterial suspension, fix the conical flask containing the bacterial suspension and sample on an oscillating shaker, and shake at 300r / min for 2min at a temperature of 20℃. Take 1.0ml of the bacterial suspension and dilute it to 100 times, take 1.0ml of the sample solution after shaking, inoculate it on the agar base, and culture it at 37℃ for 48h under natural light. Count the colonies according to the method in GB15979-2003. Calculate the antibacterial rate according to the following formula: Antibacterial rate = (average colony count before sample shaking - average colony count after sample shaking) / average colony count before sample shaking x 100%. The results are shown in Table 3.

[0067]

[0068] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 3, it can be found that the wear-resistant high-strength polyoxymethylene sheet prepared by the present invention has good antibacterial properties.

[0069] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(2-oxirane-1)methylamine are ring-opening polymerized to prepare copolymerized formaldehyde; a tertiary amine structure is introduced into the side chain of the copolymerized formaldehyde molecule; the tertiary amine structure introduced into the side chain of the copolymerized formaldehyde molecule is reacted with the chlorine atom on 3-chloromethyl-3-methyloxetane to prepare modified polyformaldehyde, and a quaternary ammonium salt structure is generated on the side chain of the modified polyformaldehyde molecule. The introduction of the quaternary ammonium salt structure can improve the mildew and antibacterial properties of the wear-resistant and high-strength polyformaldehyde sheet.

[0070] Test Example 4

[0071] Self-healing performance test

[0072] Test method: The embodiments and comparative examples were prepared into standard specimens according to ISO527-2012, and the tensile strength of the embodiments and comparative examples was tested on a universal material testing machine. A 5 mm deep and 20 mm long crack was cut in the middle of the standard specimen, and irradiated with 120 W, 302 nm wavelength ultraviolet light for 30 min to obtain the repaired specimen, and its tensile strength was tested. The self-repair rate of the embodiments and comparative examples was calculated, and the self-repair rate = (tensile strength of the specimen after repair / original tensile strength of the specimen) × 100%. The results are shown in Table 4.

[0073]

[0074] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 4 in Table 4, it can be found that the wear-resistant and high-strength polyoxymethylene sheet prepared by the present invention has good self-repairing performance.

[0075] By comparison, the self-repairing rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(oxirane-2-yl)methylamine are ring-opening polymerized to prepare copolymerized polyoxymethylene; a tertiary amine structure is introduced into the side chain of the copolymerized polyoxymethylene molecule; the tertiary amine structure introduced into the side chain of the copolymerized polyoxymethylene molecule is reacted with the chlorine atom on 3-chloromethyl-3-methyloxetane to prepare modified polyoxymethylene, and an oxetane structure is introduced into the side chain of the modified polyoxymethylene molecule; when cracks and scratches appear on the wear-resistant high-strength polyoxymethylene sheet, the oxetane structure undergoes a ring-opening reaction under the action of ultraviolet light, and combines with the polyoxymethylene molecular chain and free -CO· free radicals and -C· free radicals on cellulose to form new chemical bonds, thereby achieving a self-repairing effect.

[0076] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A wear-resistant high-strength polyoxymethylene sheet, characterized in that: The wear-resistant high-strength polyoxymethylene sheet is prepared by reacting copolymerized polyoxymethylene and 3-chloromethyl-3-methyloxetane to obtain modified polyoxymethylene; the modified polyoxymethylene, modified cubic boron nitride, modified bamboo fiber and chloroplatinic acid are melt-mixed and injection-molded to obtain the wear-resistant high-strength polyoxymethylene sheet; The copolymer formaldehyde is prepared by ring-opening polymerization of trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane and N,N-dimethyl-1-(2-oxiranyl)methylamine; The modified cubic boron nitride is prepared by polymerizing and coating bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione on cubic boron nitride; The modified bamboo fiber is prepared by reacting bamboo fiber and allyltriethoxysilane; The bamboo fiber is obtained by purifying bamboo powder with an alkali treatment solution.

2. A method for preparing a wear-resistant high-strength polyoxymethylene sheet, characterized in that: The preparation method of the wear-resistant high-strength polyoxymethylene sheet comprises the following preparation steps: (1) Add trioxymethylene, 3-glycidoxy-1,1,3,3-tetramethyldisiloxane, and N,N-dimethyl-1-(2-oxirane-1-yl)methylamine in a molar ratio of 1:(0.05-0.07):(0.06-0.08) into a reactor, stir at 68-70°C and 100-200 r / min for 30-40 min under nitrogen protection, add 0.006-0.008 times the mass of trioxymethylene initiator, continue stirring for 5-6 h, and add 0.01 The reaction was terminated by adding ~0.012 times of triethylamine, cooled to room temperature, washed with anhydrous ethanol and deionized water for 3 to 5 times respectively, and dried at 58 to 62°C for 8 to 10 hours under vacuum conditions to obtain copolymer formaldehyde; copolymer formaldehyde, 3-chloromethyl-3-methyloxetane, and hexafluoroisopropanol were mixed uniformly in a mass ratio of 1: (0.6 to 0.8): (6 to 7), stirred at 55 to 57°C and 60 to 80 r / min for 2 to 3 hours, and dried at 66 to 70°C for 8 to 10 hours under vacuum conditions to obtain modified polyformaldehyde; (2) Add bis(4-carboxyphenyl)phenylphosphine oxide and 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione in a molar ratio of 1:(0.8-0.9) to toluene with a mass ratio of 5-6 times that of bis(4-carboxyphenyl)phenylphosphine oxide, and mix them evenly to prepare a reaction solution; mix cubic boron nitride, triphenylphosphine, and toluene in a mass ratio of 1:(0.05-0.07):(38-40), ultrasonically disperse for 50-60 minutes, add the reaction solution with a mass ratio of 8-10 times that of cubic boron nitride, stir at 98-102°C and 200-300 r / min for reaction for 3-4 hours, filter, wash with anhydrous ethanol and deionized water for 3-5 times each, and dry at 69-71°C under vacuum conditions for 8-10 hours to obtain modified cubic boron nitride; (3) Mix bamboo powder and alkali treatment liquid at a mass ratio of 1: (12-14), ultrasonically disperse for 1-1.2 hours, filter, wash with deionized water until the filtrate is neutral, and dry at 66-70°C for 8-10 hours under vacuum conditions to obtain bamboo fiber; mix bamboo fiber and anhydrous ethanol at a mass ratio of 1: (40-50), ultrasonically disperse for 20-30 minutes, add 18-20 times the mass of bamboo fiber allyl silane hydrolyzate, stir at 66-70°C, 200-300 r / min for 4-5 hours, filter, wash with anhydrous ethanol 3-5 times, and dry at 72-74°C for 9-11 hours under vacuum conditions to obtain modified bamboo fiber; (4) Weigh 98-102 parts of modified polyoxymethylene, 4-5 parts of modified cubic boron nitride, 6-8 parts of modified bamboo fiber, and 0.6-1 part of chloroplatinic acid by mass; add the modified polyoxymethylene, modified cubic boron nitride, modified bamboo fiber, and chloroplatinic acid into a screw extruder for injection molding. After injection molding, keep the temperature at 78-80°C for 2-3 hours, cool to room temperature, and demold to obtain a wear-resistant and high-strength polyoxymethylene sheet.

3. The method for preparing a wear-resistant high-strength polyoxymethylene sheet according to claim 2, characterized in that: The initiator in step (1) is one of boron trifluoride ethyl ether complex and boron trifluoride butyl ether complex.

4. The method for preparing a wear-resistant high-strength polyoxymethylene sheet according to claim 2, characterized in that: The particle size of the cubic boron nitride in step (2) is 3000 mesh.

5. The method for preparing a wear-resistant high-strength polyoxymethylene sheet according to claim 2, characterized in that: The particle size of the bamboo powder in step (3) is 1200 mesh.

6. The method for preparing a wear-resistant high-strength polyoxymethylene sheet according to claim 2, characterized in that: The preparation method of the alkaline treatment solution in step (3) is as follows: sodium hydroxide, urea and deionized water are uniformly mixed in a mass ratio of 1: (1.2-1.3): (9-10) to prepare an alkaline treatment solution.

7. The method for preparing a wear-resistant high-strength polyoxymethylene sheet according to claim 2, characterized in that: The preparation method of the allylsilane hydrolyzate in step (3) is as follows: allyltriethoxysilane and anhydrous ethanol are uniformly mixed in a mass ratio of 1:(40-44), the pH value is adjusted to 4.8-5.2 with an aqueous solution of oxalic acid having a molar concentration of 1 mol / L, and the mixture is stirred at 10-30° C. and 200-300 r / min for 20-22 min to prepare the allylsilane hydrolyzate.

8. The method for preparing a wear-resistant high-strength polyoxymethylene sheet according to claim 2, characterized in that: The process parameters of the injection molding in step (4) are as follows: setting the extruder barrel temperature to 170-180°C, the screw speed to 80-100 r / min, the injection temperature to 180-184°C, the injection pressure to 50-60 MPa, the holding time to 14-16 s, and the mold temperature to 78-80°C.

Citation Information

Patent Citations

  • Polyformaldehyde engineering plastic and preparation method thereof

    CN115322514A

  • Co-polyoxymethylene resin composition, metal resin composition taking co-polyoxymethylene resin composition as raw material as well as preparation method and application of co-polyoxymethylene resin composition

    CN115850621A